Register, enumerate and diagnose. The Movements of the Casa de Orates as an instrument of management and production of scientific knowledge (1895 - 1927) - Ramírez Norambuena, Cristóbal Eduardo (Revista de Historia Social y de las Mentalidades, 2024)
This article focuses on the history of the Casa de Orates Movements, the asylum institution's main statistical register, whose production goes from 1895 to 1932. The objective is to trace its evolution over time, then proceed to an analysis to determine the main practices involved in its elaboration, the principles on which the statistical tables were built, and the main functions they fulfilled during their publication. We argue that the statistical register not only had a function related to administration but also provided a scientific fundament to alienism at the end of the 19th century and psychiatry at the beginning of the 20th century in Chile.
Keywords: Madness; movements; administration; knowledge